UNVEILING GREEN FINANCE IN KAZAKHSTAN: A STUDY ON AWARENESS AND BARRIERS TO SUSTAINABLE INVESTMENTS - A.B. Birzhanova; A. Nurgaliyeva; A. Nurmagambetova (Хабаршысы. Экономика сериясы, 2023)
Green finance has emerged as a global trend in the advancement of financial systems and Kazakhstan is not an exception. Existing literature highlights the lack of awareness as one of the impediments to fostering green growth. The purpose of article is to examine the extent of familiarity and understanding of green finance among the populace of major cities Kazakhstan, Almaty and Astana. To achieve this, we conducted a comprehensive survey among residents of Kazakhstan. Through various channels, a detailed questionnaire focusing on green finance awareness was disseminated, yielding a dataset comprising 82 responses. Main results: the level of green awareness remains low among the populace of Kazakhstan. Perceived barriers to green investments result from low level of green awareness. Findings support the hypothesis that individuals’ decision to invest is affected not only by financial, but also environmental benefits. While the current body of literature primarily concentrates on the theoretical underpinnings of green finance, practical studies are often confined to interviews with green finance professionals within financial institutions or businesses engaged in green financing. The article’s contribution is that it presents the perspectives of the general public, thus providing a novel dimension to the ongoing discourse.